Estimate the solution to the

system of these linear equations
based on the graph.
y=−x+6
y=3x−2
(2 points)

1 answer

To solve the system of equations given by \( y = -x + 6 \) and \( y = 3x - 2 \), we can estimate the solution graphically or find the point of intersection algebraically. Here, I'll describe how to do both.

Step 1: Graph the equations

  1. Equation 1: \( y = -x + 6 \)

    • This is a line with a slope of \(-1\) and a y-intercept of \(6\).
    • The y-intercept means the line crosses the y-axis at the point (0, 6).
    • Another point on the line can be found by choosing \(x = 0\): \[ y = -0 + 6 \Rightarrow y = 6 \text{ (point: (0, 6))} \]
    • Choosing \(x = 6\) gives \(y = -6 + 6 = 0 \text{ (point: (6, 0))}\).
  2. Equation 2: \( y = 3x - 2 \)

    • This is a line with a slope of \(3\) and a y-intercept of \(-2\).
    • It crosses the y-axis at the point (0, -2).
    • Choosing \(x = 0\) gives: \[ y = 3(0) - 2 \Rightarrow y = -2 \text{ (point: (0, -2))} \]
    • Choosing \(x = 1\) gives: \[ y = 3(1) - 2 = 1 \text{ (point: (1, 1))} \]

Step 2: Find the intersection point

You can find the intersection point algebraically by setting the two equations equal to each other:

\[ -x + 6 = 3x - 2 \]

Step 3: Solve for \(x\)

  1. Rearrange the equation: \[ 6 + 2 = 3x + x \] \[ 8 = 4x \] \[ x = 2 \]

Step 4: Substitute \(x\) back to find \(y\)

Now, substitute \(x = 2\) into either of the original equations. We'll use \(y = -x + 6\):

\[ y = -2 + 6 = 4 \]

Conclusion

Thus, the solution to the system of equations, or the point of intersection, is:

\[ (2, 4) \]

So, the estimated graphically and algebraically determined solution to the system of equations is \( (2, 4) \).